Strategi pembelajaran e-learning untuk ABK pada jenjang PAUD - Iza Anugerahani Riski; Syakira Nurul Fajri; Adinda Reza Maulina; Desi Puspita Sari; Adelia Eka Lauditta; Nono Hery Yoenanto; Nur Ainy Fardhana (JURNAL LENTERA ANAK, 2020)
This study aims to find out e-learning strategies for child with special needs in ECEP (Early Childhood Education Program). This research was done at Laboratorium PAUD Anak Ceria in Surabaya. E-learning strategies for child with special needs can be identified through interviews with the head of laboratory and the teacher. Based on the results of the research, e-learning strategies for child with special needs is using TLC learning system and still refers to 2013 curriculum. In e-learning based learning, the main media that parents, students, and also teachers needed are the internet and video conference application, to be able to communicate with each other (video call) and send videos of students activities at home while they’re studying. To make an efficient learning program, parents need to prepare facilities for students to acces e-learning, while teachers need to prepare the teaching material that suitable for e-learning based learning. E-learning strategies will run optimally if there is good cooperation between teachers and parents in educating and motivating students during e-learning era.